Sylvia Plath - Wagner-Martin, Linda. author. aut Link
XII, 172 p.
Keywords: Linda Wagner-Martin's emphasis in this study is the way Sylvia Plath made herself into a writer. In keeping with the critic's early ground-breaking work on American poet William Carlos Williams, she here studies elements of Plath's work with dedication to discussions of style and effect. Her close analysis of Plath's reading and her apprenticeship writing both in fiction and poetry sheds considerable light into Plath's work in the late 1960s. The book concludes with a section assessing Sylvia Plath's current standing.